What Are the Risks of Halal Cosmetic Products? - Wahyuni, Hana Catur; Khafidin, Khafidin; Voak, Adam (Journal of Digital Marketing and Halal Industry, 2023)
PT. XYZ is a company engaged in the manufacture of private-label cosmetics and skincare products in Indonesia. However, of these private labels or ‘Maklon’ products, only four out of the 151 available Maklon manufactured products have current Halal certification. This large uncertified percentage of Maklon products has given rise to a concern about the Halal bonafides of these products, which understandably leaves significant doubts regarding their suitability for personal use in consumer’s minds. As a consequence, in an attempt to ensure potential customers of the Halal quality of the cosmetics and other products produced at the Company’s facility, process researchers have deployed a Fuzzy Failure Modes and Effects Analysis. This approach has been chosen in order to determine the level of Halal risk priorities during the production of the Company’s products, and the outcomes have been subjected to a Fault-Tree Analysis to develop appropriate recommendations to transparently mitigate any potential risks. In essence, the purpose of this research was to (i) determine the critical control points influencing Halal certification, (ii) determine the priority level within the process needed to ensure strict control procedures, and (iii) to provide practical strategies to decrease the possibility of Halal risk profile.